KEDUDUKAN LIVING LAW SEBAGAI PRANATA HUKUM DALAM UNDANG-UNDANG No. 1 TAHUN 2023 TENTANG KITAB UNDANG- UNDANG HUKUM PIDANA - Redy S, Simon Albertian; Alsa, Abdul Aziz; Sembiring, Idha Apriliana (Penerbit Lafadz Jaya, 2025)
Indonesia, as an archipelagic state, is home to diverse cultures and customs, leading to a variety of customary laws. In line with the 1945 Indonesian Constitution, these customary laws are recognized and respected as part of the national legal system. In 2023, Indonesia enacted a new Criminal Code, reflecting its cultural values and moving away from the colonial-era legal framework. This shift introduces challenges, particularly regarding the integration of customary law into the national legal system. This research examines these challenges, focusing on the interaction between customary law and positive law within Indonesia's legal framework. The study adopts a normative legal research methodology, incorporating statutory, conceptual, and comparative approaches, with primary legal sources including the 1945 Constitution and Law No. 1 of 2023 on the Criminal Code. The findings suggest that customary law can fill legal gaps when existing positive law does not cover specific offenses, particularly in the investigation and prosecution stages. Offenders may be subject to customary law before being prosecuted under positive law. This study emphasizes the need for a balanced approach to integrate customary law into Indonesia's criminal justice system, ensuring both legal coherence and respect for cultural diversity.